2018
DOI: 10.1016/j.jad.2017.12.030
|View full text |Cite
|
Sign up to set email alerts
|

Global arginine bioavailability ratio is decreased in patients with major depressive disorder

Abstract: Arginine bioavailability may be decreased in MDD. This could impair the production of nitric oxide, and thus add to oxidative stress in the central nervous system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 35 publications
1
41
0
Order By: Relevance
“…These results are consistent with previous reports (Baranyi et al 2015; Hess et al 2017, Ali-Sisto et al 2018), where the authors showed decreased circulating levels of arginine and citrulline in MDD patients. No differences were observed for citrulline or arginine when comparing treatment with ketamine to placebo in healthy controls or MDD patients.…”
Section: Arginine Pathwaysupporting
confidence: 94%
See 3 more Smart Citations
“…These results are consistent with previous reports (Baranyi et al 2015; Hess et al 2017, Ali-Sisto et al 2018), where the authors showed decreased circulating levels of arginine and citrulline in MDD patients. No differences were observed for citrulline or arginine when comparing treatment with ketamine to placebo in healthy controls or MDD patients.…”
Section: Arginine Pathwaysupporting
confidence: 94%
“…The increase in arginine levels is consistent with a recent study that also found a similar increase with esketamine treatment (Rotroff et al 2016). Other antidepressants have also been shown to have an effect in this pathway, with duloxetine resulting in an increase in the circulating levels of citrulline in a study with 12 MDD patients, while bupropion was associated with higher arginine levels in a study with 6 MDD patients (AliSisto et al 2018). The results of the study clearly demonstrate that ketamine is modulating the bioavailability of arginine in responders to ketamine treatment and that the nitric oxide cycle may be a potential mechanism of action of ketamine in responders to ketamine treatment.…”
Section: Arginine Pathwaymentioning
confidence: 99%
See 2 more Smart Citations
“…Decreased coagulation in PTSD [10] Global Arginine Bioavailability Ratio (GABR) Metabolite ↓ ↑ ↑ GABR is decreased in patients with MDD [33]; previous decreased PTSD finding published in [34] GammaglutamyltyrosineMetabolite ↑ ↑ ↑ Gammaglutamyltyrosine negatively correlated with leukocyte telomere length [35] heart rate Physiological ↑ ↑ ↑ Elevated heart rate following trauma associated with development of PTSD [36] hsa-miR-133a-3p miRNA ↓ ↓ ↓ hsa-miR-192-5p miRNA ↓ ↓ ↑ Abundant in liver; associated with obesity and diabetes [37,38] hsa-miR-424-3p miRNA ↓ ↓ ↓ miR-424-3p has been associated with inflammation [39] hsa-miR-9-5p miRNA ↓ ↓ ↓ Enriched in brain tissue and regulates neurogenesis [40] Insulin Clinical Labs ↑ ↑ ↑ Increased insulin resistance in veterans with PTSD [41] ITIH2-VQF Protein ↓ ↓ ↓…”
Section: Validation Of a Robust Multi-omic Ptsd Biomarker Panelmentioning
confidence: 99%